“YANG-TETAP” DAN “YANG-BERUBAH” DALAM PERSPEKTIF METAFISIKA PANCASILA - Djoko Pitojo (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2007)
The paper will tries to review classical debate about “the stable” and “the change” and discuss every notion in their variants. Description about the debate among philosophers will express chronologically as possible. Last but not least, it tries to express “the stable” and “the change” in Philosophy of Pancasila perspective. Pancasila, in its position as a genetivus objectivus, is very interesting to interpreted continuously; in order to do it, we must neither to maintain “the stabile” as a “glorious” in the one hand nor merely want to make it “change” in the other hand. For both attitudes are naïve and irresponsible. Pancasila, as a life symbol, must be actualized and interpreted openly, dialogically and there is no place for monopoly in interpretation. While, Pancasila as a genetivus subjectivus, give answer to the developing and management of state problems, unavoidably, the changes are always as assumption. “The stable” is “being” itself with its identity and developing; and that is meaning its existence. The ethical implication, therefore, is commitment to values inhering on the existence of being itself. “The change” is the way to handle of being and its technical management.